Characteristics of Solid-State Lasers with Passive Q-Switching by Polymer Saturable Absorbers - Bezrodnyi, V.I.; Ishchenko, A.A.; Negriyko, A.M.; Yaskovets, A.O.; Demidovich, A.A.; Danailov, M.B.; Orlovich, V.A.; Shpak, P. (Ukrainian Journal of Physics, 2022)
The characteristics of miniaturized diode-pumped compact passively Q-switched Nd:YAG and Nd: YVO4 lasers have been studied. Lasing at a wavelength of 1.064 μm with a pulse repetition rate of up to 25 kHz, a pulse duration of 2–5 ns, an average power of 130 mW, and a pump power of 3.5 W was realized with the use of a polymer Q-switch on the basis of polyurethane doped with the bis-(4-dimethylaminodithiobenzyl)-nickel dye. Diode-pumped solid-state mini lasers with passive Q-switching by sandwich-type modulators are efficient compact sources of short powerful light pulses with a high optical quality of the beam.